Semaglutide in the treatment of nonalcoholic fatty liver disease and nonalcoholic steatohepatitis - Magdalena Mazurek; Edyta Białowąs; Ewelina Dybała; Iwona Cuber; Artur Aghadi (Kazimierz Wielki University, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is an increasing problem in the modern world due to increased morbidity and due to its clinical consequences. It is a chronic liver disease, histologically divided into non-alcoholic steatohepatitis (NAFL) with isolated steatosis to non-alcoholic steatohepatitis (NASH), which is characterized by hepatocyte injury, inflammation, and variable degrees of fibrosis that can progress to cirrhosis in a fraction of patients. Data on the prevalence of NAFLD vary depending on the population studied and the method used to establish the diagnosis, but the prevalence rate ranges from 6% to 35%, with a median of 20%. The prevalence of NASH in the European population is estimated at 5-6%, which makes NAFLD a new civilizational challenge. Aim of the study: The following article as an analysis of the current medical knowledge on the effectiveness and safety of NAFLD and NASH treatment with semaglutide based on available publications. Methods and materials: Literature review based on PubMed data using the following key words: NAFLD; NASH; semaglutide; Glucagon-like peptide-1 (GLP-1) analogues State of knowledge: GLP-1 receptor agonists are incretin drugs. This class of drugs has been approved by the FDA for the treatment of type 2 diabetes. Results: There is currently no approved therapy for NAFLD or nonalcoholic steatohepatitis (NASH). Beneficial effect of semaglutide on glycemia and weight loss makes them an attractive potential therapeutic form in NASH. However, there is a need for more clinical studies, on larger groups of people to recognize the effective form of semaglutide NAFLD therapy.